2018
DOI: 10.1186/s12943-018-0833-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq profiling of circular RNAs in human laryngeal squamous cell carcinomas

Abstract: Abnormal expression of non-coding circular RNAs (circRNAs) have been reported in many types of tumors. circRNA have been suggested to be an ideal candidate biomarker for diagnostic and therapeutic implications in cancers. The aim of this study was to assess the circRNA expression profile of laryngeal squamous cell carcinomas (LSCC). The biopsy samples from patients with LSCC were obtained intra-operatively. The circRNA expression was performed using secondary sequencing. Among 10 patients with LSCC, 2 were wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…Studies have shown that circRNA has important regulatory effects in a variety of biological processes, especially in the occurrence, development, and metastasis of various malignant tumors [22][23][24]. circRNA expression profiling revealed a series of differentially expressed cir-cRNAs in LSCC tissues [25,26], suggesting that cir-cRNA may have important roles in the occurrence and progression of LSCC. In this study, we performed largescale RNA sequencing of LSCC and matched ANM tissues, and established the circRNA, miRNA, and mRNA expression profiles of LSCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that circRNA has important regulatory effects in a variety of biological processes, especially in the occurrence, development, and metastasis of various malignant tumors [22][23][24]. circRNA expression profiling revealed a series of differentially expressed cir-cRNAs in LSCC tissues [25,26], suggesting that cir-cRNA may have important roles in the occurrence and progression of LSCC. In this study, we performed largescale RNA sequencing of LSCC and matched ANM tissues, and established the circRNA, miRNA, and mRNA expression profiles of LSCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…After integrating the comparison results of "moderately differentiated LSCC vs ANTs" and "well differentiated LSCC vs ANTs", there were 18 consistently downregulated circRNAs and 5 upregulated circRNAs in Table 4 The potential function and the mechanism of the dysregulated circRNAs in HNCs Note: HNSCC head and neck squamous cell carcinoma, OSCC oral squamous cell carcinoma, LSCC laryngeal squamous cell carcinoma, HSCC hypopharyngeal squamous cell carcinoma, NPC nasopharyngeal carcinoma, "-" means not investigated in the paper, "*" means based on bioinformatics analysis but not validated experimentally LSCC. Moreover, the downregulation of hsa_circ: chr20:31876585-31,897,648 with most predicted target miRNAs was validated by qRT-PCR, demonstrating its potential as a diagnostic biomarker for LSCC [171]. However, the results need to be verified in a larger group because the sample size of this study was small, and the dysregulated circRNAs with the largest change-fold were not discussed.…”
Section: Circrnas In Lsccmentioning
confidence: 84%
“…Recently, NGS was conducted to investigate the cir-cRNA profiles in LSCC, which could account for the cir-cRNAs that are not present on the microarray [171]. Three moderately differentiated LSCC samples, two well-differentiated LSCC samples and five corresponding ANT samples were included.…”
Section: Circrnas In Lsccmentioning
confidence: 99%
“…The significant function of lncRNAs has been widely acknowledged, with recent evidence confirming that lncRNAs play an important role in carcinogenesis and tumor metastasis [23,24]. Up-and downregulated lncRNAs may be important molecular markers for cancer diagnosis, therapy and tumor metastasis [25][26][27].…”
Section: Discussionmentioning
confidence: 99%